Surface runoff of horse grazed pasture – a disregarded hydrological response unit in low mountain ranges - Chifflard, Peter; Moulding, Dennis; Petri, Jann-Thorben; Zemke, Julian J.; Reiss, Martin (DIE ERDE – Journal of the Geographical Society of Berlin, 2018)
Accurate prediction of surface runoff is of vital interest for flood prediction which in turn requires the process knowledge about key factors affecting its temporal and spatial variability. Antecedent soil moisture and grazing intensity have been detected as important factors, but there exists no explicit field study investigating the spatial and temporal variability of surface runoff generation on horse grazed pasture. In our study, for the first time the surface runoff generation on horse grazed pasture was analyzed using a rainfall simulator along with measurements of soil water content and soil physical properties. The results were compared with concurrent investigations on cattle grazed pasture land. The analyses of 8 rainfall simulations on 1 m² plots at a rate of 46.6 mm/h revealed mean runoff coefficients ranging from 0.9% to 50.5%. The most important findings of our study are that the antecedent soil moisture distinctly impacts the amount of surface runoff and the runoff coefficient is significantly higher on horse grazed pasture than on cattle grazed pasture. These results underline the importance of further experimental studies to obtain a broader process knowledge about this specific hydrological response unit, especially in regard to the increasing portion of horse grazing in the low mountain ranges.